PENGARUH PENAMBAHAN PROSES INOKULASI TERHADAP STRUKTUR MIKRO DAN KEKERASAN PRODUK COR DENGAN MATERIAL FC 250 - Sabtun Ismi Khasanah; Zikri Niamillah, Muhammad; Aditya Mardani, Danis; Suparni, Suparni (LPPM Politeknik Manufaktur Ceper, 2024)
The inoculation process in metal casting is needed to make grey cast iron or nodular cast iron. Inoculation aims to increase the number of freezing nuclei and promotes the formation of a homogeneous microstructure. This research aims to determine the effect of the inoculation addition process on the microstructure and hardness of PP products with FC-250 material. The changes made include changes to the inoculation process and changes to the chemical composition of the induction furnace. Changes in the inoculation process include changing the inoculation process which was initially only carried out on ladles with an inoculation material weight of 0.5 kg to 2 processes, namely on ladles with an additional weight of 0.8 kg of inoculation material and an inoculation process on crucible (kowi) with an additional material weight of 0.4 kg. The results of the metallography test after the additional inoculation process showed that the pearlite and ferrite graphite spread evenly and fell into Type-A graphite. The hardness test results show that the effect of adding inoculation changes the level of hardness so that it complies with ASTM 40 specifications/standards, namely 180 – 302 HB. The hardness value after the addition of the inoculation process was 190 HB.